THE EMERGENCE FACTORS AND ACTIVITY CHARACTERISTICS OF THE MORPHOLOGICAL SCIENTIFIC SCHOOL IN THE IVANO-FRANKIVSK STATE MEDICAL INSTITUTE IN THE 1940-90S - Децик, О. З.; Клим, І. М.; Стовбан, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The laws of appearance and development of morphological scientific school of Ivano-Frankivsk State Medical Institute are investigated in the article. The social causes and individual motives of basic scientific achievements of its representatives are found out. The basic methodological approaches and empirical methods are analyzed. Results of their scientific activity are classified.